Hubungan Bimbingan Belajar dengan Sikap, Minat, Motivasi dan Prestasi Belajar Siswa SMU - Abdul Hadis (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
This correlational study was intended to examine the relationship between study guide and students’ attitudes, interests, motivation, and achievement. Thirty second-year students of SMUN 9 and 30 of SMUN 14 Makassar were selected at random. The instruments used to collect the data were an achivement test, questionnaires, interviews, and observation. The data were analyzed using descriptive statistics as well as regression and qualitative analyses. The findings indicate that the students’ attitudes, interests, and learning motivation were of low category and that their achievement was fair. Attitudes, interests, and motivation were found to have positive correlations with students’ achievement; study guide was also found to have effects on students’ attitudes, interests, motivation, and achievement.